2016
DOI: 10.3389/fmicb.2016.01587
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Goose with Genotype VIId Newcastle Disease Virus of Goose Origin Elicits Strong Immune Responses at Early Stage

Abstract: Newcastle disease (ND), caused by virulent strains of Newcastle disease virus (NDV), is a highly contagious disease of birds that is responsible for heavy economic losses for the poultry industry worldwide. However, little is known about host-virus interactions in waterfowl, goose. In this study, we aim to characterize the host immune response in goose, based on the previous reports on the host response to NDV in chickens. Here, we evaluated viral replication and mRNA expression of 27 immune-related genes in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 48 publications
5
24
0
Order By: Relevance
“…Fourteen AvBDs have been identified in chickens to date, and are considered as key components of the host innate immune response against pathogens, and potentially provide a link between innate and adaptive immunities. In agreement with the present observations, expression levels of AvBDs were upregulated in tissues of various avian species infected with NDV strains of pigeon or goose origin (Li et al., ; Xu et al., ), as well as with other avian viruses (Ma et al., , ; Xu et al., ). However, differences in their expression levels in chickens infected with different NDV strains have not previously been studied.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Fourteen AvBDs have been identified in chickens to date, and are considered as key components of the host innate immune response against pathogens, and potentially provide a link between innate and adaptive immunities. In agreement with the present observations, expression levels of AvBDs were upregulated in tissues of various avian species infected with NDV strains of pigeon or goose origin (Li et al., ; Xu et al., ), as well as with other avian viruses (Ma et al., , ; Xu et al., ). However, differences in their expression levels in chickens infected with different NDV strains have not previously been studied.…”
Section: Discussionsupporting
confidence: 92%
“…TLRs can respond to viral infection in both mammals and birds, and produce antiviral factors that help inhibit viral replication (Kapczynski et al., ; Li et al., ; Xu et al., ). Consistent with this observation, the present study showed that expression levels of most TLRs were significantly upregulated in some chicken tissues at 48 hr after infection with either GD or F48E9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a study of the Zhong et al [49] has demonstrated the upregulation of the viperin (an IFN stimulated gene) in the DEFs and also in the spleen, kidneys, liver, brain, and blood of Changbai ducks infected with G7 APMV-1 through intranasal or intramuscular route. Experimental infection of geese with genotype VII APMV-1 upregulate the expression of TLR 1-3, 5, 7, and 15, avian β-defensin 5-7, 10, 12, and 16, IL-8, IL-18, IL-1β, and IFN-γ, and MHC class I in different tissues [50].…”
Section: Experimental Infection Studies Of Ducks and Geese With Apmv-1mentioning
confidence: 98%